Pengaruh Debt to Equity Ratio (DER), Asset Growth (AG), dan Firm Size (FS) terhadap Dividen Payout Ratio (DPR) (Suatu Kajian Studi Literatur Manajemen Keuangan Perusahan) - Hilaria Rosdiana Keban; Henny A. Manafe; Stanis Man (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
Previous or appropriate scientific work will be useful for other scientific work, especially those that discuss the subject of each variable or other factors that influence that variable. This scientific work describes the literature review and the factors that affect the dividend payout ratio (DPR), namely the debt-to-equity ratio (DER), asset growth (AG), and firm size (FS). This review intends to ensure the hypothesis that results in each variable provide benefits for subsequent writing. The results of this writing emphasize if: 1) DER has a positive or important impact on the DPR; 2) AG has a positive or important impact on the DPR; 3) FS has a positive or important impact on the DPR; 4) DER, AG, and FS simultaneously have positive and meaningful impacts on the DPR.